2020
DOI: 10.1101/2020.09.22.308965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-reactive serum and memory B cell responses to spike protein in SARS-CoV-2 and endemic coronavirus infection

Abstract: Pre-existing immune responses to seasonal endemic coronaviruses could have profound consequences for antibody responses to SARS-CoV-2, either induced in natural infection or through vaccination. Such consequences are well established in the influenza and flavivirus fields. A first step to establish whether pre-existing responses can impact SARS-CoV-2 infection is to understand the nature and extent of cross-reactivity in humans to coronaviruses. We compared serum antibody and memory B cell responses to coronav… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
92
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 45 publications
13
92
1
Order By: Relevance
“…Although other groups have reported the existence of SARS-CoV-2 cross-reactive neutralizing antibodies in sera from individuals who were not infected with SARS-CoV-2, the neutralization activity observed appears low [ 11 , 12 ]. Unlike other reports, the prepandemic sera used in our study that have undetectable neutralization activity against SARS-CoV-2 can neutralize seasonal HCoVs, in some cases quite potently.…”
Section: Discussionmentioning
confidence: 99%
“…Although other groups have reported the existence of SARS-CoV-2 cross-reactive neutralizing antibodies in sera from individuals who were not infected with SARS-CoV-2, the neutralization activity observed appears low [ 11 , 12 ]. Unlike other reports, the prepandemic sera used in our study that have undetectable neutralization activity against SARS-CoV-2 can neutralize seasonal HCoVs, in some cases quite potently.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, non-RBD S1 as well as S2binding neutralizing antibodies have been identified for both SARS-CoV and SARS-CoV-2 (92,165,(180)(181)(182). As of this moment, two studies have shown evidence that the presence of sCoV antibodies is associated with less severe COVID-19 symptoms (183,184), while two more have shown some neutralizing activity in pre-pandemic samples (118,165).…”
Section: Protection From Sars-cov-2 Infections By Scovs Antibodiesmentioning
confidence: 99%
“…A significant challenge in developing a specific SARS-CoV-2 serological assay is the potential for cross-reactivity of SARS-CoV-2 capture antigens with antibodies against other human CoVs (163). SARS-CoV-2 shares amino acid sequences and antigenic T and B cell epitopes with the highly prevalent sCoVs that cause the common cold including 229E, OC43, NL63, and HKU1, and also with the now rare MERS and extinct SARS-CoV that both cause severe and fatal respiratory disease ( Figure 2) (62,(164)(165)(166)(167)(168). A recent prevalence survey of the sCoVs using RT-PCR revealed that OC43 is the most prevalent sCoV followed by NL63, HKU1, and finally 229E (169).…”
Section: Cross-reactivity Of Sars-cov-2 Antibodies To Seasonal Covsmentioning
confidence: 99%
See 2 more Smart Citations